2016
DOI: 10.1039/c5tx00165j
|View full text |Cite|
|
Sign up to set email alerts
|

A possible new mechanism and drug intervention for kidney damage due to arsenic poisoning in rats

Abstract: Arsenic poisoning is a worldwide endemic disease that affects thousands of people. Currently, the aetiology of the disease is known, but its pathogenesis is uncharacterized and there is no specific treatment. We established a rat model of coal-burning arsenic poisoning by feeding the animals corn powder baked with high arsenic coal. By observing subsequent changes in kidney and immune function, we found that arsenic induces both kidney and immune damage. Furthermore, there is a significant correlation between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 17 publications
0
30
0
Order By: Relevance
“…In a pro-inflammatory environment, Treg cells release IL-17A; in the absence of inflammation, TGF-β promotes Treg differentiation to maintain immune tolerance [62,63]. Thus, in considering the effect of Gingko biloba treatment on the immune suppression and kidney damage in arsenic poisoned rats [29] and the results of this study, we conclude that GBE has a role in the balance of the Th17/Treg axis and shifts this balance to produce an anti-inflammatory effect. For arsenicosis patients, their inflammatory imbalance can be modified to restore immune homeostasis, thereby improving their immune function.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…In a pro-inflammatory environment, Treg cells release IL-17A; in the absence of inflammation, TGF-β promotes Treg differentiation to maintain immune tolerance [62,63]. Thus, in considering the effect of Gingko biloba treatment on the immune suppression and kidney damage in arsenic poisoned rats [29] and the results of this study, we conclude that GBE has a role in the balance of the Th17/Treg axis and shifts this balance to produce an anti-inflammatory effect. For arsenicosis patients, their inflammatory imbalance can be modified to restore immune homeostasis, thereby improving their immune function.…”
Section: Discussionmentioning
confidence: 63%
“…Gingko biloba has been used to enhance immune function in arsenic-poisoned rats and to relieve kidney damage [29]. We followed up 74 arsenicosis patients who received a course of 3-month placebo or GBE therapy.…”
Section: Gbe Attenuates Arsenicosis-induced Disruption Of the Th17/trmentioning
confidence: 99%
See 1 more Smart Citation
“…1 It is well-known that the kidney is the main organ of the urinary system that is primarily responsible for arsenic excretion; as such, its structure and function are vulnerable to damage. Renal dysfunction caused by arsenic has been demonstrated with epidemiologic investigations 11,12 as well as in animal studies, 13,14 mainly affecting the function of proximal convoluted tubules and glomeruli. Recent studies 9,15 in Taiwan have also revealed the relationship between arsenic exposure and chronic arsenic disease.…”
Section: Introductionmentioning
confidence: 98%
“…8 Moreover, a large number of animal experiments and epidemiological data demonstrate that chronic exposure to arsenic can damage the immune system and ultimately lead to immune dysfunction. 9 12…”
Section: Introductionmentioning
confidence: 99%